Country image and consumer-based brand equity: relationships and implications for international marketing - Pappu, Ravi; Quester, Pascale G; Cooksey, Ray W (Journal of International Business Studies, 2007)
This paper examines the relationships between consumers’ country-level and product-level images of a country, and the equity they associate with a brand from that country, using canonical correlation analysis. Results from mallintercept surveys conducted in an Australian state capital city indicated that the consumer-based equity of a brand was significantly associated with both the macro and micro images of the country of origin of the brand. The relationship between these two sets of constructs was found to be positive as well as product category specific. Furthermore, each consumer-based brand equity dimension contributed differently to the relationship according to the product category, while the contribution of both country image dimensions (macro and micro) was also product category specific. Results also showed that cars, as a product category, are more sensitive to country image than televisions. These findings have direct and important implications for international marketers.